Pediatric hydatid cyst with ventricular aneurysm and surgical treatment with dor procedure, case report - Durmaz, Ayşegül; Düzyol, Çağrı; Gür, Sibel; İlkeli̇, Ekin; Omay, Oğuz (Journal of cardiac surgery, 2022)
Background Cardiac involvement of hydatid cyst disease (HCD) is a rare presentation but may lead to life‐threatening complications such as cyst rupture and should be treated surgically. Methods A 10‐year‐old male patient with cranial and complicated cardiac HCD lesions that caused lower extremity peripheral arterial occlusion and aneurysmatic dilatation in the left ventricular apex is presented. Results Although the patient was in the pediatric age group, the Dor procedure was successfully applied to preserve the ventricular geometry. The Dor procedure for a ventricular aneurysm caused by a cardiac hydatid cyst (CHC) was rarely applied in the pediatric age group. Conclusion In conclusion, this case differs from other CHCs previously reported in the literature due to the advanced stage of the disease, atypical clinical presentation, and rare complications despite the young age of the case. The surgical method used in treating the patient makes the subject more interesting.